Thiết kế và sử dụng thẻ Flashcard trong dạy học nhằm phát triển năng lực giải quyết vấn đề và sáng tạo cho học sinh tiểu học - Nguyễn, Diệp Ngọc; Ngô, Thị Kim Hoàn; Đỗ, Thị Ngọc Quỳnh (Tạp chí Giáo dục, 2025)
In the current context of globalization, coupled with the development of artificial intelligence (AI), the acquisition of knowledge is no longer a problem for learners. However, how to apply that knowledge to solve reallife problems, especially in dangerous and urgent situations, always poses a challenging question for learners, particularly for elementary school students. Problem-solving and creativity are among the core competencies that need to be cultivated for elementary students according to the requirements of the 2018 General Education Program. These competencies can be developed through a system of situational flashcards. Using situational flashcards as a teaching tool aims to increase learning interest and promote problem-solving and creativity skills for primary school students. Within the scope of this article, the author presents the process of designing flashcards and using flashcards in escape scenarios to develop problem-solving and creativity skills for primary school students.